2007
DOI: 10.1105/tpc.106.045724
|View full text |Cite
|
Sign up to set email alerts
|

Improperly Terminated, Unpolyadenylated mRNA of Sense Transgenes Is Targeted by RDR6-Mediated RNA Silencing in Arabidopsis

Abstract: RNA silencing can be induced by highly transcribed transgenes through a pathway dependent on RNA-DEPENDENT RNA POLYMERASE6 (RDR6) and may function as a genome protection mechanism against excessively expressed genes. Whether all transcripts or just aberrant transcripts activate this protection mechanism is unclear. Consistent RNA silencing induced by a transgene with three direct repeats of the b-glucuronidase (GUS) open reading frame (ORF) is associated with high levels of truncated, unpolyadenylated transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
222
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(233 citation statements)
references
References 60 publications
9
222
0
2
Order By: Relevance
“…Position-effect variegation is a well-documented concept in Drosophila, but very little is known about it in Arabidopsis, where the 35S promoter of virus origin has been extensively employed in transgenesis. The variation of the expression level of a transgene driven by this strong and constitutive promoter has been attributed largely to a gene-specific RNA-silencing mechanism (Schubert et al 2004;Luo and Chen 2007). The impact of position effects on the variation of the expression pattern of a transgene driven by a tissue-or stage-specific plant promoter was less documented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Position-effect variegation is a well-documented concept in Drosophila, but very little is known about it in Arabidopsis, where the 35S promoter of virus origin has been extensively employed in transgenesis. The variation of the expression level of a transgene driven by this strong and constitutive promoter has been attributed largely to a gene-specific RNA-silencing mechanism (Schubert et al 2004;Luo and Chen 2007). The impact of position effects on the variation of the expression pattern of a transgene driven by a tissue-or stage-specific plant promoter was less documented.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that insulators have evolved from promoters (Raab and Kamakaka 2010). The gypsy insulator downstream from the terminator region of transgenes might ensure correct termination of reporter transcripts, because it was documented that RNA silencing triggered by mRNA 39 readthrough was a major cause of reduced expression of transgenes in plants (Luo and Chen 2007). However, terminator activity for the gypsy insulator was recently tested in Drosophila, where it was found not to function (Silicheva et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, when a transgene without a terminator or with a poor terminator was introduced into a plant genome, aberrant transcripts without polyA tails accumulated, leading to induction of RNA-DEPENDENT RNA POLYMERASE6 (RDR6)-dependent RNA silencing (Luo and Chen 2007). Those authors also reported that silencing was relieved, and the expression level of the gene concomitantly increased, by a double terminator that promoted accurate polyadenylation of mRNA.…”
mentioning
confidence: 87%
“…Boyko et al (2010b) showed that acute exposure to various types of stresses results in the transient change of the 35S promoter-driven transgene expression, whereas chronic exposure to stress does not lead to any significant changes. Additionally, it is known that most terminators used in plant science, such as NOS, 35S, and G7, are somewhat leaky and can lead to read-through transcription (Rose and Last, 1997;Luo and Chen, 2007;Ü lker et al, 2008) or even supply cryptic intron splice sites (Ü lker et al, 2008). Since the sequence details are missing from publications that make use of the SHR lines, it has not been possible to analyze whether these sequences could have stochastic-or pathogen-induced promoter, terminator, or intron activities.…”
Section: Read-through Transcriptionmentioning
confidence: 99%